A comparison between exact and DWBA stripping to a resonance - Brinati, JoséR.; Bund, Gerhard W. (Elsevier, 1978)
Exact cross sections for deuteron stripping to a resonance from a heavy target were obtained by solving the Faddeev-Lovelace equations for separable s-wave potentials. The s-wave resonance in the neutron-target subsystem is described by an energy-dependent term in the potential, of the type arising from a BSEC. The DWBA is derived without recourse to an adjustable optical potential. The DWBA and exact cross section, without the background contribution, are evaluated and compared. Interference effects between the resonance and background amplitudes turned out to be important and of the kind observed experimentally. © 1978.